Traditional Games as Ethnopedagogy in the Deep Learning Approach to Strengthening the Character of Elementary School Students - Yetni Marlina; Hasrul Hasrul; Nutfah A.M Arif (Alpatih Harapan Semesta, 2026)
Strengthening the character of elementary school students has become a crucial issue in 21st-century education amidst technological developments and the declining internalization of local cultural values. However, learning in elementary schools still tends to be oriented towards cognitive aspects, thus not optimally shaping students’ character holistically. This study aims to review the literature on traditional games as a source of ethnopedagogy in a deep learning approach to strengthening the character of elementary school students. The research method uses a literature review to analyze various scientific articles, proceedings, and relevant documents sourced from the Google Scholar and Garuda search engines. The study results show that traditional games contain cultural, social, moral, and collaborative values, which are sources of ethnopedagogy that can support deep learning. Integrating traditional games into learning as ethnopedagogy can strengthen elementary school students’ character traits, such as cooperation, discipline, responsibility, social awareness, tolerance, creativity, and empathy. Furthermore, the deep learning approach makes the learning process more contextual, reflective, and centered on student experience.